09.24 Phone a friend?. Issue 12 (14th November 2019) - Minton, Thomas; Fuller, Geraint; Rinaldi, Simon; Fehmi, Janev; Bosnell, Rose; Barton, Eleanor
Abstract : A 72-year-old man with type 2 diabetes mellitus was admitted under nephrology with malaise. He was diagnosed with acute kidney injury secondary to urinary retention and hydronephrosis. Over 10 days during this admission he developed progressive symmetrical limb paraesthesia and weakness with areflexia. Neurophysiological studies demonstrated a severe demyelinating polyneuropathy with widespread motor slowing and prolonged distal motor latencies. CSF was acellular with a protein of 5.9 g/L. He was treated with IV immunoglobulins and stabilised for 2 weeks. He then deteriorated over the next four weeks despite IV methylprednisolone, oral corticosteroids and 5 cycles of plasma exchange. He had profound limb weakness (0/5) and required ventilation. He had hypoalbuminaemia, with 1.5 g proteinuria consistent with a nephrotic syndrome. We phoned a friend. IgG4 anti–contactin-1 (CNTN1) antibodies were identified in serum with a CNTN1 at 1:1600. He received 4 cycles of Rituximab. After 6 weeks he was off ventilation with grade 4 power in both arms. Recently autoantibodies against node of Ranvier proteins have emerged in a subset of patients with CIDP. These patients have a homogenous clinical phenotype with an aggressive polyneuropathy, proteinuria and poor response to conventional therapy, but seem to respond to other agents, including Rituximab and Cyclophosphamide.